2015
DOI: 10.1371/journal.pone.0143954
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Knock-Down of the Mineralocorticoid Receptor in Mice Disturbs Regulation of the Renin-Angiotensin-Aldosterone System and Attenuates Heart Failure Induced by Pressure Overload

Abstract: Mineralocorticoid receptor (MR) inactivation in mice results in early postnatal lethality. Therefore we generated mice in which MR expression can be silenced during adulthood by administration of doxycycline (Dox). Using a lentiviral approach, we obtained two lines of transgenic mice harboring a construct that allows for regulatable MR inactivation by RNAi and concomitant expression of eGFP. MR mRNA levels in heart and kidney of inducible MR knock-down mice were unaltered in the absence of Dox, confirming the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Lysates were prepared from BMDM in denaturating sample buffer containing a protease inhibitor cocktail (RIPA with NP40, NA 3 VO 4 , and Na 3 MoO 4 ) and heated at 95°C for 5 min ( 22 ). 15 µg proteins were separated on a 7.5% SDS-PAGE gel, transferred to a nitrocellulose membrane (Amersham, Braunschweig, Germany) and stained with a rabbit anti-MR or a rabbit anti-ERK antibody (both 1:1,000, Santa Cruz, Heidelberg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lysates were prepared from BMDM in denaturating sample buffer containing a protease inhibitor cocktail (RIPA with NP40, NA 3 VO 4 , and Na 3 MoO 4 ) and heated at 95°C for 5 min ( 22 ). 15 µg proteins were separated on a 7.5% SDS-PAGE gel, transferred to a nitrocellulose membrane (Amersham, Braunschweig, Germany) and stained with a rabbit anti-MR or a rabbit anti-ERK antibody (both 1:1,000, Santa Cruz, Heidelberg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…It is generally assumed that the major physiological role of the MR is the regulation of the salt-water balance and various cardiac functions. For example, an ubiquitous inactivation of the MR or its conditional ablation in kidney or cardiomyocytes altered the control of sodium reabsorption and blood pressure, and partially protected from cardiac failure ( 19 22 ). Furthermore, specific deletion of the MR in myeloid cells was also found to protect against cardiac hypertrophy, fibrosis, and heart failure, suggesting that the MR in immune cells is more important than previously supposed ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although functions of MR in several other cell types have been elucidated in pathologic cardiac hypertrophy and heart failure, [15][16][17]19,[36][37][38] the roles of MR in T cells have not been illuminated. Through this study, we demonstrated that eplerenone and TMRKO attenuated POL-induced cardiac remodeling and dysfunction in parallel with attenuated cardiac inflammation, as well as decreased T-cell accumulation and activation in the heart.…”
Section: Discussionmentioning
confidence: 99%
“…Most transgenic rats survived to adulthood providing a rodent model of pseudo-hyperaldosteronism that could be assessed in future studies. A more elegant RNAi-based MR knockdown transgenic model has been recently created by the same group using a doxycycline induced MRshRNA approach in mice (Montes-Cobos et al 2015). This transgenic model used the Tet-repressor to block expression of an MRshRNA transgene that would only become active when adult mice were treated with doxycycline.…”
Section: Knockdown Of Mr Levels In Vivo By Antisense Mrna or Rnai Appmentioning
confidence: 99%